Impact of Body Mass Index and Comorbidities on Health-Related Quality of Life and Work Productivity in People With Overweight or Obesity: A Survey-Based Study in the United Kingdom - Andrea Leith; Lewis Harrison; João Diogo da Rocha Fernandes; Lise M. Hagelund; Christopher Lübker; Silvia Capucci (Journal of Health Economics and Outcomes Research, 2025)
**Background:** The prevalence and socioeconomic impact of obesity are increasing in the United Kingdom; however, the effects of body mass index (BMI) and comorbidities on health-related quality of life (HRQoL) and work productivity in people living with overweight or obesity (PLwO) have not been fully described. **Objective:** To assess self-reported HRQoL and work productivity in PLwO in the United Kingdom, grouped by BMI and presence of cardiovascular and/or metabolic (CVM) comorbidities. **Methods:** Data used were from the Adelphi Obesity Disease Specific Programme™, a real-world cross-sectional survey (October 2023–April 2024). Physicians reported demographic and clinical characteristics for PLwO on a weight management program who were ≥18 years old and had current or previous BMI ≥30 kg/m2, or ≥27 kg/m2 with ≥1 weight-related comorbidity. The same PLwO completed the 36-item Short-Form Health Survey version 2 (SF-36v2) and Work Productivity and Activity Impairment: Specific Health Problem (WPAI:SHP) questionnaire. **Results:** Physicians provided data for 904 PLwO, of whom 119 completed the survey questionnaires. Mean age for PLwO was 51.7 years, 54% were women, the majority were White (69%), and 70% had ≥1 CVM comorbidity. SF-36v2 physical functioning scores were lower with higher BMI (P < .05). Scores for physical functioning, role limitations due to physical problems, bodily pain, general health, vitality, and the physical component summary were lower (_P_ < .05) in PLwO with cardiovascular comorbidities than in those without. PLwO with metabolic comorbidities had lower scores than those without for physical problems, general health, social functioning, mental health, and the mental component summary (_P_ < .05). WPAI:SHP scores for activity impairment, presenteeism, and overall work impairment were higher in PLwO with CVM comorbidities than in those without (_P_ < .05), indicating lower productivity. **Discussion:** Increasing BMI may be linked to lower physical functioning in PLwO. Comorbidities were associated with reductions in HRQoL, with different domains affected depending on the type of comorbidity. These comorbidities were also associated with impaired work productivity. **Conclusion:** The presence of comorbidities, along with BMI, are important considerations for managing obesity. Reducing the prevalence of overweight or obesity is likely to benefit both individuals and wider society.